Exploring Multicultural Family Dynamics: An Analysis of Family Dysfunction in Mochtar Lubis’s Senja di Jakarta - Mafi Sri Wahyu Tiara; Ahmad Bahtiar (Universitas PGRI Sumatera Barat, 2024)
The characters representing couples and the familial system portrayed in Mochtar Lubis's novel